2016
DOI: 10.2300/acari.25.suppl_179
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of essential oils of medicinal plants at reducing the amounts of allergen produced by the European house dust mite, <i>Dermatophagoides pteronyssinus</i> (Trouessart)

Abstract: Essential oils obtained from three medicinal plant species, namely, cinnamon (Cinnamomum bejolghota [Buch.-Ham.] Sweet), citronella grass (Cymbopogon nardus Rendle), and clove (Syzygium aromaticum [L.] Merr. & L. M. Perry), were sprayed on allergenic materials (house dust plus spent mite medium produced by the European house dust mite, Dermatophagoides pteronyssinus [Trouessart]) to evaluate the effects of the oils on allergen levels. A 1% solution of each essential oil in 95% ethanol was sprayed on the allerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
1
5
0
1
Order By: Relevance
“…The toxicity of EOs obtained from 13 selected medicinal plants, citronella grass, lemongrass, cinnamon, clove, black pepper, eucalyptus, star anise, ginger, sweet fennel, kaffir lime, cassumunar ginger, siam cardamom, and sweet basil in emulsions against adult African red mites revealed that EO emulsions of citronella grass, lemongrass, cinnamon, and clove at 2% were highly effective in killing the African red mite with more than 70% mite mortality (Figure 1). This concurred with the report by Insung et al (2016), who found that EOs of citronella grass, clove, cinnamon, and lemongrass were extremely toxic against the European house dust mite (Dermatophagoides pteronyssinus). The clove EO also exhibited high insecticidal activity against adult thrips (Frankliniella schultzei) and mealybugs (Pseudococcus jackbeardsleyi) (Pumnuan and Insung, 2016b).…”
Section: Resultssupporting
confidence: 91%
“…The toxicity of EOs obtained from 13 selected medicinal plants, citronella grass, lemongrass, cinnamon, clove, black pepper, eucalyptus, star anise, ginger, sweet fennel, kaffir lime, cassumunar ginger, siam cardamom, and sweet basil in emulsions against adult African red mites revealed that EO emulsions of citronella grass, lemongrass, cinnamon, and clove at 2% were highly effective in killing the African red mite with more than 70% mite mortality (Figure 1). This concurred with the report by Insung et al (2016), who found that EOs of citronella grass, clove, cinnamon, and lemongrass were extremely toxic against the European house dust mite (Dermatophagoides pteronyssinus). The clove EO also exhibited high insecticidal activity against adult thrips (Frankliniella schultzei) and mealybugs (Pseudococcus jackbeardsleyi) (Pumnuan and Insung, 2016b).…”
Section: Resultssupporting
confidence: 91%
“…Sweet), citronella grass ( Cymbopogon nardus Rendle), and clove ( Syzygium aromaticum [L.] Merr. & L. M. Perry) lowered allergenic properties of Der p 1, one of the key allergenic proteins in Dermatophagoides pteronyssinus , and suggested that it results from reduced allergen levels [ 36 ]. Thus, the impact of todomatsu oil on allergen amount was examined using SDS-PAGE.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have been undertaken to demonstrate the importance of HDM allergens exposure, especially for respiratory allergic diseases [ 54 , 55 ]. In contrast, although HDM was recognized as a known allergic source, little attention was attracted to the investigation of inhibiting its allergens [ 36 ]. Insung et al (2016) [ 36 ] reported that essential oils obtained from medicinal plants cinnamon ( Cinnamomum bejolghota [Buch.-Ham.]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Una de las formas más eficientes para masificar la producción de una especie pura de ácaro es su cultivo en condiciones controladas de laboratorio. Los cultivos puros de B. tropicalis pueden tener diferentes aplicaciones, como su utilización en la evaluación de la actividad acaricida de diferentes sustancias (Cuca, Mendoza-Mena, Álvarez-Caballero, Macías-Villamizar & Coy-Barrera, 2012;Insung, Pumnuan, Mahakittikun & Wangapai, 2016), producción de extractos alergénicos (Yi, Chew, Jiménez, Chua & Lee, 1999;Fernández-Caldas, 2013), anticuerpos (Labrada et al, 2002;Yang et al, 2003), purificación de alérgenos específicos (Cardona, Eraso, Serna, Guisantes & Martínez, 2004) y desarrollo de pruebas diagnósticas o para el monitoreo de los alérgenos a nivel ambiental (Tsay, Williams, Mitchell & Chapman, 2002). El objetivo de este estudio fue evaluar las propiedades inmunoquímicas de extractos alergénicos de B. tropicalis obtenidos a partir de cultivos puros del ácaro.…”
unclassified